Study on the Advantages and Strategies of Film and Television Works in Promoting the Communication of Social Work: An Analysis based on the Case "Nezha 2" - Tian, Peidong (International Journal of Social Sciences and Public Administration, 2025)
The construction of Chinese-style modernization has become an important issue today, and the happiness and well-being of the people have become an important value orientation of the socialist modernization construction, which is also the ultimate goal of promoting high-quality development. Social work is an important path to promote social stability and people's happiness, which can solve social contradictions, protect vulnerable groups, improve public services, and promote social harmony. However, due to the lack of public understanding of social work, many people think it is just simple charity or the responsibility of the government, ignoring its complexity and necessity. This has led to insufficient attention and support for the importance of social work, and the professional image and status of social workers are relatively low. Therefore, it is necessary to strengthen the dissemination and promotion of social work, so that the public can recognize the importance and necessity of social work, improve the status of social work and public support, and improve the professional image and social status of social workers, so as to make greater contributions to the realization of social stability and people's happiness. This article uses the popular audiovisual work "Nezha 2" as a typical case, and analyzes and discusses the positive impact and strategies of audiovisual works on the dissemination of social work. The study found that in the dissemination of social work, audiovisual works, with their strong appeal and infectiousness, have deeply explored the relevant knowledge of social work, vividly conveying the concepts of social work, and the omnimedia function and efficient and fast production and distribution methods of audiovisual works can help the knowledge of social work be widely disseminated through multiple channels, promoting public participation and support. Based on the above analysis, this article proposes some policy strategies from the perspectives of the government, academia, and social workers, in the hope of contributing to the dissemination of social work.